MODEL ATRIBUT MINIMARKET DI LINGKUNGAN KAMPUS MENURUT MAHASISWA UNPAR DAN MARANATHA BANDUNG - Fransisca Mulyono (Research Report - Humanities and Social Science, 2012)
Research Purpose – the purpose of this research is to see what minimarket’s attributes on campuses are perceived important by students of Unpar and Maranatha, Bandung. The result is models on minimarket attributes around the two campuses mentioned above.Methodology – a review of current store attribute literatures reveal 61 attributes considered important by the researchers to then distributed to the students UNPAR and Maranatha as the respondents.Findings – data analysis showed the difference in the models, where five main priority Unpar’s minimarket attribute model consists of: promotions, staff, appearance, relaxation and product organizing dimensions. While the five highest priority Maranatha’s minimarket attribute model are: attitude of employees, security, promotion, minimarket access, and relaxation dimensions.Orijinalitas –because of research on minimarket attribute on campus as far as researchers know is rare, so this study was conducted to make the model in the range of minimarket attributes around Unpar and Maranatha campuses, Bandung.Keywords – store attribute, minimarket attribute, minimarket on campuses, EFA.